Human Amniotic Membrane Is Not Suitable for the Grafting of Colon Lesions and Prevention of Adhesions in a Xenograft Rat Model. (August 2017) - Barski, Dimitri; Gerullis, Holger; Ecke, Thorsten; Varga, Gabriella; Boros, Mihaly; Pintelon, Isabel; Timmermans, Jean-Pierre; Otto, Thomas
Introduction . New biological materials are needed for specific applications in reconstructive bowel surgery and for the prevention of adhesion formation. Amniotic membranes (AMs) are assumed to have a number of unique characteristics that enhance the ingrowth of the surrounding tissue. The aim of the present study was to provide proof of these qualities in a xenograft model. Materials and methods . A multilayer human AM (HAM) was applied to repair defined colon wall defects in Sprague-Dawley rats (n = 18). The control group was repaired with a suture (n = 6). The animals were killed humanely at 7, 21, and 42 days after implantation. Adhesions and perioperative complications were examined. Histological and immunohistological analyses were performed to assess a number of parameters, including degradation of the HAM, inflammation, graft rejection, and smooth muscle ingrowth. Results . Two rats in the treated group died. No other severe complications were observed. Adhesion formation was more prominently visible in the HAM group ( P < .05). The initially increased inflammation in the HAM group reduced over time but remained significantly increased ( P < .05). The HAM degraded over time and a subtle transient glomerulitis could be observed. Conclusion . HAMs were found to increase adhesion formation and were not suitable for bowel augmentation in the presented xenograft model.